SOCIO-ECONOMIC EFFICIENCY ANALYSIS OF THE SKI RESORT PROJECT «KOK-ZHAILAU» - A. Kondybayev,; G.Taspenova, (Academic Journal of Physical and Chemical Sciences, 2019)
In this article is shown the natural and climatic peculiarities of Almaty, which has a positive impact on the formation of tourist and recreational complex and especially on the creation of the ski resort "Kok-Zhailau". The organization of the resort will contribute to the tourist and recreational development of the territory and provide employment of the local population. There was investigated the analysis of development factors of the ski resort complex "Kok-Zhailau" and made the justification of the priority directions, which are necessary for realization of the concept of the region’s tourism development. It is shown that the natural and climatic peculiarity has a positive impact on the formation of the tourist and recreational complex of the region, and especially on the creation of the ski resort "Kok-Zhailau". The organization of the complex will contribute to the tourist and recreational development of the territory and employment of the local population.